Chimeric immune checkpoint protein vaccines inhibit the tumorigenesis and growth of rat cholangiocarcinoma - Pan, Yi-Ru; Wu, Chiao-En; Huang, Wen-Kuan; Chen, Ming-Huang; Lan, Keng-Hsueh; Yeh, Chun-Nan (Frontiers in Immunology, 2022)
Cholangiocarcinoma (CCA) is the second most common primary liver malignancy and carries a dismal prognosis due to difficulties in achieving an optimal resection, and poor response to current standard-of-care systemic therapies. We previously devised a CTLA4-PD-L1 DNA cancer vaccine (DNA vaccine) and demonstrated its therapeutic effects on reducing tumor growth in a thioacetamide (TAA)-induced rat intrahepatic CCA (iCCA) model. Here, we developed a CTLA4-PD-L1 chimeric protein vaccine (Protein vaccine), and examined its effects in the rat iCCA model. In a therapeutic setting, iCCA-bearing rats received either DNA plus Protein vaccines or Protein vaccine alone, resulting in increased PD-L1 and CTLA-4 antibody titers, and reduced iCCA tumor burden as verified by animal positron emission tomography (PET) scans. Treating iCCA-bearing rats with Protein vaccine alone led to the increase of CTAL4 antibody titers that correlated with the decrease of tumor SUV ratio, indicating regressed tumor burden, along with increased CD8 and granzyme A (GZMA) expression, and decreased PD-L1 expression on tumor cells. In a preventive setting, DNA or Protein vaccines were injected in rats before the induction of iCCA by TAA. Protein vaccines induced a more sustained PD-L1 and CTLA-4 antibody titers compared with DNA vaccines, and was more potent in preventing iCCA tumorigenesis. Correspondingly, Protein vaccines, but not DNA vaccines, downregulated PD-L1 gene expression and hindered the carcinogenesis of iCCA. Taken together, the CTLA4-PD-L1 chimeric protein vaccine may function both as a therapeutic cancer vaccine and as a preventive cancer vaccine in the TAA-induced iCCA rat model.